Sustainability Ratings and the Disciplinary Power of the Ideology of Numbers - Chelli, Mohamed; Gendron, Yves (2013)
The main purpose of this paper is to better understand how sustainability rating agencies, through discourse, promote an “ideology of numbers” that ultimately aims to establish a regime of normalization governing social and environmental performance. Drawing on Thompson’s (Ideology and modern culture: Critical social theory in the era of mass communication, 1990) modes of operation of ideology, we examine the extent to which, and how, the ideology of numbers is reflected on websites and public documents published by a range of sustainability rating agencies. Our analysis indicates that the ideology of numbers promotes a relatively narrow vision of corporate social and environmental responsibility. That is, it establishes some areas of visibility while leaving in the shadow certain aspects of the ways in which companies fulfill, or fail to meet, their social and environmental responsibilities. The ideology of numbers also exerts power by identifying those companies that are deemed to be worthy of inclusion, or not, in a supposedly socially responsible corporate elite.
Keywords: Sustainability; rating agencies; Mechanisms of exclusion; Ideology of numbers; Discourse Analysis; Disciplinary power